Cultural values affect functional food perception. Issue 8 (5th August 2019) - Neupane, Saugat; Chimhundu, Ranga; Chan, K.C.
Abstract : Purpose: The purpose of this paper is to investigate the relationship between consumers' cultural values and their functional food perception. Design/methodology/approach: The research is qualitative in nature and uses the grounded theory method. The data were collected through in-depth interviews with three ethnic groups, Anglo-Australian, Chinese and Indian ethnic groups in Australia. The constant comparative data analysis approach was used to analyse the interview text. Findings: The results indicate that there is a relationship between consumers' cultural values and their functional food perception. Functional food perception depends upon the consumers' predisposition towards their culture, their motives for functional food consumption and the level of perseverance towards functional foods. Research limitations/implications: The study includes only three ethnic groups and is qualitative in nature, which may limit its generalisability to the universe. The inclusion of more ethnic groups and additional sources of data could form directions for future research. Practical implications: Functional food marketers can assess the kind of cultural values the ethnic groups in Australia uphold and capture those values in their marketing strategies. The cultural values in the framework could be used for the segmentation of functional food consumers. In a multicultural setting like Australia, segmentation of consumers based on the standard values would be more feasible and effective to target consumers spread across different ethnic groups but who uphold similar values. Originality/value: The research has attempted to fill the gap in the existing literature about the relationship between culture and functional food perception. The latent variables in the theoretical framework proposed by the qualitative enquiry can be a good starting point for understanding the influence of cultural values on functional food perception and the development of a more comprehensive theoretical framework for functional food behaviour.